Erratum: Pengaruh Small-Sided Games Terhadap Kapasitas Aerobik (Vo2 Max) Pemain Sepakbola - Oman Hadiana; Didi Muhtarom; Dani Nurdiansyah (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.635 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.